2005
DOI: 10.1038/sj.bmt.1704956
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A and Mycophenolate Mofetil vs Cyclosporine A and Methotrexate for graft-versus-host disease prophylaxis after stem cell transplantation from HLA-identical siblings

Abstract: Summary:The combination of Cyclosporin A (CSA) and Methotrexate (MTX) is considered to be the standard regimen for the prevention of graft-versus-host disease (GVHD) after stem cell transplantation (SCT) from HLA-identical siblings. Mycophenolate Mofetil (MMF) has been widely used for GVHD prophylaxis after nonmyeloablative SCT, but experience following myeloablative therapy is still limited. We retrospectively compared CSA/MTX and CSA/MMF in 93 patients (median age 35 years, range 17-59 years, male subjects 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 24 publications
5
60
1
3
Order By: Relevance
“…In line with several studies comparing the introduction of MMF instead of MTX as GVHD prophylaxis in Table 2 Cause of death according to the GVHD prophylaxis allo-HSCT, 5,10,21 in this retrospective study we report a similar incidence of GVHD and possibly a somewhat improved toxicity profile in favor of the CsA/MMF combination. It is important to note, however, that earlier studies comparing the impact of such combinations on the toxicity profile, the incidence of GVHD and transplantrelated mortality, had considerable limitations.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In line with several studies comparing the introduction of MMF instead of MTX as GVHD prophylaxis in Table 2 Cause of death according to the GVHD prophylaxis allo-HSCT, 5,10,21 in this retrospective study we report a similar incidence of GVHD and possibly a somewhat improved toxicity profile in favor of the CsA/MMF combination. It is important to note, however, that earlier studies comparing the impact of such combinations on the toxicity profile, the incidence of GVHD and transplantrelated mortality, had considerable limitations.…”
Section: Discussionsupporting
confidence: 72%
“…In combination with CsA, it has shown a good safety profile in phase II trials. 5,10,11 However, no differences in the rate of acute GVHD (aGVHD) were obtained after conventional high-dose allo-HSCT compared with standard CsA/MTX prophylaxis. 10,11 A recent study by Neumann et al 5 showed that CsA/MMF was as efficient as CsA/MTX for GVHD prophylaxis, but with faster hematopoietic recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Studies on the use of MMF as part of GVHD prophylaxis have been limited in size and mostly inconclusive, as most investigators reported insufficient plasma levels of the active metabolite MPA. [3][4][5]8,24,25 Most of these studies revealed a favorable toxicity profile of combinations of MMF with calcineurin inhibitors compared to regimens incorporating MTX. Encouraging results were reported by Nash et al, 7 who demonstrated that the rate of GVHD Targeting mycophenolate mofetil for GVHD prophylaxis I Haentzschel et al after transplantation from matched-sibling donors could be significantly reduced by using higher MMF doses up to 60 mg/kg daily.…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing Tac and MMF to Tac and MTX in both sibling and unrelated donor myeloablative HCT also demonstrated no difference in 100 day incidence of grade 2-4 GVHD, with a significant reduction in toxicities, but a higher incidence of grade 3-4 GVHD, primarily in unrelated donor transplants [15]. Additional small retrospective studies evaluating MMF in myeloablative transplant recipients have also confirmed improved toxicity and GVHD incidence and survival outcomes that are comparable to MTX [16,17]. On the basis of these data, we have routinely employed MMF in myeloablative MSD donor allogeneic HCT for GVHD prophylaxis at our institution.…”
Section: Introductionmentioning
confidence: 96%